Community Participation on the Self Help Group of Methane Gas (Biogas) Management as Renewable Energy in Indonesia - Prayitno, Gunawan; Hakim, Annisah Nurul; Meidiana, Christia (International Journal of Energy Economics and Policy, 2020)
This study focuses on social capital as an opportunity for community engagement in the management of methane gas (biogas) as renewable energy, which the Self Help Group carries out on the final disposal site in Supit Urang. Methane gas generated from well-managed sites can provide positive advantages that can be used as an energy source (specially for cooking) for the local community as a replacement for LPG. Community participation in biogas management from methane gasses may improve public welfare, particularly in landfill capture and distribution. The Social Networks Analysis shall be used to determine the Rate of Participation (RoP), density and centrality of group involvement. The findings of the RoP study suggest that the concentration of participant affiliation to organizations influences the low level of participation. Density analysis reveals that when the respondent follows more than one organizations and entities, network density value is high, so the respondents can be more interlinked. Centrality analysis shows that measuring degree centrality by UCINET reveals that six respondents have the same high value and the same low central value. The median centrality is 0.58, reflecting the value of respondents and organizations. Keywords: Social Capital, Biogas (methane gas), Self Help Group, Social Network Analysis (SNA), RoP, Density, Centrality JEL Classifications: A13, C89, Q15, R14 DOI: https://doi.org/10.32479/ijeep.10595